Workplace harassment in the General Direction of Ports of Colombia (DGPC) defense sector entity (2014)
In Colombia the Workplace bullying took an important step towards recognizing explicitly the issue of Law 1010 of 2006, which seeks to raise awareness and humanization of labor relations and therefore, good treatment by any of hierarchical levels of public and private entities. Given that this law establishes “the decent and fair working conditions, freedom, privacy, honor, mental health, harmony among those who share the same work environment and good business environment